Expression and clinical significance of CA125, CA153 and CEA in nipple discharge of breast cancer patients: CA125, CA153, CEA in Breast Cancer Nipple Discharge: Significance - Geng, Jun; Shi, Jinli; Guo, Weina; Li, Haiyan; Yang, Dan; Gao, Yan (Journal of Medical Biochemistry, 2023)
Background: It is an important clinical means to identify benign and malignant breast diseases caused by nipple discharge through the detection and analysis of components in nipple discharge. This study was aimed to test the expression and clinical significance of carbohydrate antigen 125 (CA125), carbohydrate antigen 153 (CA153) and carcinoembryonic antigen (CEA) in nipple discharge of breast cancer patients. Methods: From January 2017 to December 2018, 86 patients with invasive ductal carcinoma of the breast with nipple discharge (breast cancer group) and 50 patients with ordinary breast duct hyperplasia with nipple discharge (benign control group) were selected, and the nipple discharge and serum CA125, CA153 and CEA levels in the two groups were detected by electrochemiluminescence immunoassay.Results: The nipple discharge and serum CA125, CA153 and CEA levels in the benign control group were significantly lower than those in the breast cancer group, and the serum CA125, CA153 and CEA levels were obviously lower than those nipple discharge levels. The expression levels of CA125, CA153 and CEA in nipple discharge in the breast cancer group had no significant difference in different age of onset and different tumor sites. The CA125, CA153 and CEA levels in nipple discharge of patients with tumor diameter n5 cm, low differentiation, high stage, metastasis, and recurrence were obviously elevated versus to those of patients with tumor diameter
Keywords: breast cancer; CA125; CA153; CEA; nipple discharge